METHODS OF PRICING ACCORDING TO THE LAW OF SUPPLY AND DEMAND (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This work highlights the historical development of the theory of supply and demand, its place in the system of Economic Thought and its practical significance. The article analyzes theoretical principles formulated by economists such as Aristotle, Adam Smith, David Ricardo, Alfred Marshall. Also, the essence of the laws of supply and demand, their interdependence, their impact on market equilibrium and the methods of pricing are explained by practical examples.ation: this work highlights the historical development of the theory of supply and demand, its place in the system of Economic Thought and its practical significance. The article analyzes theoretical principles formulated by economists such as Aristotle, Adam Smith, David Ricardo, Alfred Marshall. Also, the essence of the laws of supply and demand, their interdependence, their impact on market equilibrium and the methods of pricing are explained by practical examples. The diagrams analyzed supply and demand curves, price equilibrium, and price differences across regions. The study found that supply and demand laws play an important role in ensuring resource allocation and price stability as the primary mechanism of a market economy.